2019
DOI: 10.1088/1742-6596/1407/1/012042
|View full text |Cite
|
Sign up to set email alerts
|

Zero and Near Zero Power Intelligent Microsystems

Abstract: The Near Zero Power RF and Sensor Operations (N-ZERO) program from DARPA has created a new, nanowatt class of intelligent sensors and RF receivers enabling systems that are passive or nearly passive while operating in an intelligent standby mode. Such systems can be persistently powered by small batteries for many years or perpetually via miniature energy harvesters. The program sought wake-up receivers with a sensitivity of -100dBm and physical sensors that could classify vehicles at a range of 10 m, with pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…[ 38 ] Importantly, and with far reaching industrial applications, the picowatt power expense of these MOF‐based active materials far exceed DARPA's 10 nW threshold for near‐zero power applications. [ 8 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 38 ] Importantly, and with far reaching industrial applications, the picowatt power expense of these MOF‐based active materials far exceed DARPA's 10 nW threshold for near‐zero power applications. [ 8 ]…”
Section: Resultsmentioning
confidence: 99%
“…[ 7 ] By decreasing power requirements to “near‐zero” (<10 nW), robust, long‐lived sensing could be achieved in a wider range of environments. [ 8 ] While nanogap‐style architectures have been shown successful for near‐zero power detection of some organics, [ 9 ] the incorporation of nanoporous metal–organic frameworks (MOFs) offer an attractive alternative.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such power consumption is way below the near‐zero power applications threshold of 10 nW, as defined by “The Near Zero Power RF and Sensor Operations (N‐ZERO) program from DARPA”. [ 44 ] To quantify the sensing performance, the change in current ratio, R = ( I air − I gas )/ I air × 100% is calculated and plotted in Figure a–c for sensors with a diameter of 100, 200, 300 nm and pitch size of 1000 nm (D100P1000, D200P1000, D300P1000). It can be clearly observed that the sensing response increases dramatically with decreasing of NW diameter.…”
Section: Resultsmentioning
confidence: 99%
“…[40,41] It was also reported that indium phosphide (InP) epitaxial layer could achieve ≈0.1 ppm level sensitivity to NO 2 at relatively lower working temperature (80-150 °C) indicating their potential for room-temperature NO 2 sensing. [42][43][44] Most of the reports on InP NO 2 sensor focused on planar structure, [45][46][47] while their nanostructures have rarely been studied.…”
Section: Introductionmentioning
confidence: 99%